Deteksi Timbal (Pb), Kadmium (Cd) Dalam Ikan Kelabau (Osteochilus melanopleura Bleeker), Ikan Seluang (Rasbora argyrotaenia Bleeker) Dan Ikan Baung (Mystus nemurus C&V) Dari Pasar Induk Kota Palangka Raya, Indonesia - Edison Harteman; - Aunurafik (Fakultas Peternakan Universitas Kristen Palangka Raya, 2013)
Grass Carp (Osteochilus melanopleura Bleeker 1852) is herbivorous fish; Silver Rasbora (Rasbora argyrotaenia Bleeker 1849) is omnivorous fish; Catfish (Mystus nemurus C & V) is carnivorous live in freshwater habitats. This study was aimed to evaluate the concentration of Pb and Cd in the gills, liver, kidney, muscle and muscle blood fish released. The samples of fish were taken from the central market of Palangka Raya city. The concentration of Pb and Cd were analyzed by using Atomic Absoption Spectrophotometer (AAS). The results showed that the concentrations of Pb and Cd in the liver is ≥ kidney> gill> muscle> muscle whose blood was removed. The concentration of Pb and Cd in Silver Rasbora is > Catfish > Grass Carp. The concentration of Pb and Cd in fish muscle blood issued less than muscle whose blood does not removed.